Increased Retention of Gadolinium in the Inflamed Brain After Repeated Administration of Gadopentetate Dimeglumine: A Proof-of-Concept Study in Mice Combining ICP-MS and Micro– and Nano–SR-XRF. Issue 10 (October 2019) - Wang, Shuangqing; Hesse, Bernhard; Roman, Marco; Stier, Deborah; Castillo-Michel, Hiram; Cotte, Marine; Suuronen, Jussi-Petteri; Lagrange, Adrien; Radbruch, Helena; Paul, Friedemann; Taupitz, Matthias; Schellenberger, Eyk; et al.
Abstract : Objectives: The aim of this study was to determine in vivo if brain inflammation leads to increased gadolinium (Gd) retention in brain tissue after repeated applications of Gd-based contrast agents (GBCAs). Materials and Methods: Experimental autoimmune encephalomyelitis (EAE) was induced in female SJL/J mice (n = 6). Experimental autoimmune encephalomyelitis and healthy control mice (n = 4) received 2.5 mmol/kg Gd-DTPA over 10 days (8 injections, cumulated dose of 20 mmol/kg), starting at day 14 post immunization when EAE mice reached the maximal clinical disability. In a group of mice, T1-weighted 2-dimensional RARE images were acquired before the first GBCA injection and 1 day after the last injection. Mice were killed either 1 day or 10 days after the last Gd application. From each single animal, a brain hemisphere was used for Gd detection using inductively coupled plasma mass spectrometry, whereas the other hemisphere was processed for histology and synchrotron x-ray fluorescence spectroscopy (SR-XRF) analysis. Results: Gadolinium deposition in inflamed brains was mapped by SR-XRF 1 day after the last Gd-DTPA injections, although only mild signal hyperintensity was found on unenhanced T1-weighted images. In addition, using inductively coupled plasma mass spectrometry, we detected and quantified Gd in both healthy and EAE brains up to 10 days after the last injections. However, EAE mouse brains showed higher levels of Gd (mean ± SD, 5.3 ± 1.8 μg/g; range, 4.45–8.03 μg/g) with respect to healthy controls (mean ± SD, 2.4 ± 0.6 μg/g; range, 1.8–3.2 μg/g). By means of micro–SR-XRF, we identified submicrometric Gd hotspots in all investigated samples containing up to 5893 μg Gd/g tissue. Nano–SR-XRF further indicated that Gd small hotspots had an average size of ~160 nm diameter and were located in areas of high inflammatory activity. Conclusions: After repeated administrations of Gd-DTPA, ongoing inflammation may facilitate the retention of Gd in the brain tissue. Thus, neuroinflammation should be considered as a risk factor in the recommendation on use of linear GBCA-enhanced MRI. Abstract : Supplemental digital content is available in the text.